articel EVALUATING THE IMPACT OF SUSTAINABILITY REPORTING ON CORPORATE FINANCIAL PERFORMANCE - Nida Garnida Fitrianti; Anggun Yolistina; Zaenal Aripin (Journal of Jabar Economic Society Networking Forum, 2024)
Background:Sustainability reporting has become an essential aspect of corporate governance, driven by the increasing demand for transparency in environmental, social, and governance (ESG) practices. As companies face growing pressure from investors, regulators, and consumers to adopt sustainable practices, the need to understand the impact of sustainability reporting on corporate financial performance has never been more critical. Aims:This study aims to evaluate the relationship between sustainability reporting and corporate financial performance, focusing on the role of environmental, social, and governance factors in influencing financial outcomes. By examining data from publicly listed companies across various industries, this research seeks to identify the key drivers of financial success linked to sustainability practices. Research Method:A mixed-methods approach was employed, combining quantitative analysis of financial data from 50 publicly listed companies spanning from 2015 to 2023, with qualitative insights gathered through semi-structured interviews with industry experts. Key financial metrics such as return on assets (ROA), return on equity (ROE), and earnings per share (EPS) were analyzed in relation to ESG scores derived from third-party rating agencies. Results and Conclusion:The study found a positive correlation between sustainability reporting and improved financial performance, particularly in sectors such as technology and services. Environmental initiatives, such as carbon reduction and resource efficiency, were found to have the most significant impact on return on assets and equity. Social responsibility investments also contributed to enhanced market capitalization, while strong governance practices reduced stock price volatility. The findings suggest that companies adopting comprehensive sustainability practices tend to experience better financial outcomes, greater investor confidence, and improved stakeholder relationships. Contribution:This research contributes to the growing body of literature on sustainability and corporate performance by providing empirical evidence on the financial benefits of sustainability reporting. The study also offers practical recommendations for companies looking to enhance their sustainability practices and improve financial performance through effective ESG reporting.